Reorganization of Active Surveillance of Acute Flaccid Paralysis (AFP) in Emilia-Romagna, Italy: a two-step Public Health intervention - Palandri, Lucia; Morgado, Mariana; Colucci, Maria Eugenia; Affanni, Paola; Zoni, Roberta; Mezzetta, Sandra; Bizzarro, Assunta; Veronesi, Licia (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: The International Health Regulations Emergency Committee declared in 2014 that poliovirus circulation is a public health emergency of international concern. In 2017 and 2018 Italy was classified at intermediate risk of poliovirus reintroduction based on suboptimal poliovirus surveillance. Acute flaccid paralysis active surveillance is the gold standard in the polio eradication process. The aims of this study were to investigate the causes of reduced acute flaccid paralysis case reporting in Emilia-Romagna in the last few years (step 1) and to study a public health intervention to restore an adequate level of acute flaccid paralysis surveillance in that region (step 2). Methods: In the first step a context analysis was performed by analysing the 2015-2017 Hospital Discharge Registers in Emilia-Romagna with the ICD-9-CM differential diagnosis codes for acute flaccid paralysis. Data from context analysis was then used to plan a new regional collaborative network of acute flaccid paralysis active surveillance. Results: The active surveillance network was, at the end of the study, composed by 49 doctors from both hospital administrations and clinical wards from 4 University Hospitals and 7 Local Health Authorities throughout the Region. In 15 months, 7 acute flaccid paralysis cases have been reported; 85,7% received a full clinical and virological investigation and 83,3% completed the 60 day’s follow-up. The mean response to each e-mail was 48,5% (SD 7,5%). Conclusions: In 2019, the Emilia-Romagna’s active surveillance system reached the sensitivity, completeness of case investigation and follow-up required to achieve the minimum levels for certification standard surveillance.